[ÁrpÁd Bacsa 2]
cartoon, in the open-air, wedding, children play, combi-trabant, Eger, christmas, karate-competition, 1976 Salgó speedway-race, skating competition in the TV, flowers, winter scene, baby, track race, flower-carnival